An Analysis of SBAS Signal Reception in Space. Issue 3 (27th September 2016) - Kahr, Erin; Montenbruck, Oliver; O'Keefe, Kyle
Abstract: WAAS, EGNOS, GAGAN, and MSAS data have been collected from the CanX‐2 CubeSat. The suitability of SBAS for navigation in geostationary orbits (GEO), where SBAS satellites may be permanently in view, was assessed. The analysis revealed that all tracked SBAS transmit enough power to be tracked over Earth's limb. GAGAN has the narrowest gain pattern, WAAS has a similar pattern to EGNOS but a 2–4 dB higher transmit power, and MSAS has the lowest signal power but more even global coverage, with stronger power transmitted towards the edge of the Earth. SBAS ranging typically agrees with GPS single‐point positions to within +/−10 m for WAAS and +/−20 m for MSAS and GAGAN. It was determined that the SBAS ranging capability is useable in GEO and other high orbits, provided that fast correction data are applied to the broadcast ephemeris, and the lower accuracies are accounted for. Copyright © 2016 Institute of Navigation